Morphometric relations in the grey eel catfish Plotosus canius in the coastal waters of Port Dickson, Peninsular Malaysia - Usman, B. I.; S. M. N. Amin; Arshad , A.; Kamarudin, M. S. (Triveni Enterprises, 2016)
Samples of grey eel catfish Plotosus canius were collected from the coastal waters of Port Dickson, Malaysia from January to December, 2012. A total of 341 specimens (172 males and 169 females) were used to estimate the length-weight relationship parameters. Mean population size of females were 0.72 cm taller than the males, however difference was not significant (t-test, P > 0.05). The overall relationship equations between total length (TL) and body weight (BW) were established for males as Log TW = 2.71 Log TL ? 1.85 (R2 = 0.95) and for females as Log TW = 2.88 Log TL ? 2.10 (R2 = 0.95). The estimated relative growth co-efficient (b) values were 2.71 for males and 2.88 for females. It is revealed that growth pattern of the species showed negative allometry. In both males and females, relationship between TL and SL gave highest regression coefficient (0.99). While relationship between TL and EL gave lowest regression coefficient in both males and females (0.87 and 0.81 respectively). The findings from this study contributed first information on morphometric relations of the fish from Malaysian coastal waters and could be useful for sustainable management options of P. canius in Malaysia.